POTENSI PENYEBARAN AIR LINDI HASIL TPA PADA KUALITAS AIR TANAH SEKITAR - Arfani, Nabila Nur; Purnomo, Yayok Suryo (ENVIROSAN : Jurnal Teknik Lingkungan, 2023)
Environmental pollution can occur because leachate from waste disposal has many parameters that can harm the environment at high or large concentrations. It seems that the Ketapang TPA is not perfect in terms of leachate and waste management where this TPA still does not have a leachate tank or tub. This study aims to determine the potential for leachate release into the surrounding environment by considering the quality of leachate from the Ketapang landfill and the quality of groundwater around the Ketapang landfill which is located in Sampeng Regency. This study also aims to determine the health status of residents who use groundwater by sending questionnaires to several residents who routinely use groundwater for their daily activities. The method for determining groundwater intake points is by purposive sampling method. Furthermore, a correlation analysis of groundwater quality around the TPA was carried out with the distance of the groundwater sample to the TPA location. The results showed that leachate at Ketapang TPA contained COD parameters of 2692 mg/L, pH 9.7, Cadmium which was <0.0204 mg/L, TSS 780 mg/L, and Total N 254.4 mg/L. Then the groundwater around the Ketapang TPA contains COD, Total N, and Cadmium parameters which exceed the quality standards.